2020
DOI: 10.1108/ijoem-09-2019-0717
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate effect on money demand in Pakistan

Abstract: PurposeThis paper aims to examine association of money demand with key macroeconomic variables in Pakistan. The paper also investigates the asymmetric effect of real effective exchange rate (REER) on money demand.Design/methodology/approachThe study employs both linear autoregressive distributed lag (ARDL) and non-linear autoregressive distributed lag (NARDL) model. Annual data from 1970 to 2018 is used which is subjected to non-linearity through partial sum concept. Empirical analysis is conducted to prove if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
4
1
Order By: Relevance
“…In developing markets, such as Indonesia, it was found that the rupiah exchange rate had a positive effect on the demand for money in the long and short terms. However, this study contradicts this and is not relevant to previous publications, such as Bahmani-Oskooee, Bahmani, Kutan, and Xi (2019); Mahmood and Alkhateeb (2018); McGibany and Nourzad (1995) and Zehra, Kashif, and Chhapra (2021), which state that the demand for money is influenced by the exchange rate.…”
Section: Discussioncontrasting
confidence: 95%
“…In developing markets, such as Indonesia, it was found that the rupiah exchange rate had a positive effect on the demand for money in the long and short terms. However, this study contradicts this and is not relevant to previous publications, such as Bahmani-Oskooee, Bahmani, Kutan, and Xi (2019); Mahmood and Alkhateeb (2018); McGibany and Nourzad (1995) and Zehra, Kashif, and Chhapra (2021), which state that the demand for money is influenced by the exchange rate.…”
Section: Discussioncontrasting
confidence: 95%
“…So, at higher exchange rates, the value of agricultural goods and services would also rose within the period of study. Zehra et al (2020) noted that with increasing trade liberalization, capital market globalization, adoption of flexible exchange rate regime, innovation and technological advancements, central banks around the globe are now more than ever concerned in establishing determinants of money demand. This arises from the fact the exchange rate affects money demand for key sectors of an economy.…”
Section: Results Of Var Of Adgp Ms2 and Lnxrmentioning
confidence: 99%
“…This arises from the fact the exchange rate affects money demand for key sectors of an economy. According to Zehra et al (2020), money demand has been empirically observed to respond asymmetrically to macroeconomic indicators like inflation, interest rate and exchange rate, with resultant effect on the overall economy. Also, Ho and Saadaoui (2020) reported empirical results from Vietnam that when the exchange rate shock is symmetric, the money demand increases by 3.7 percent in the long term; when the shock is asymmetric, there was an increase of 15.6 percent in the money demand; and for a permanent nominal depreciation of one percent, there was a decrease of 7.4 percent in the money demand.…”
Section: Results Of Var Of Adgp Ms2 and Lnxrmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Ogundipe et al (2014), the conservative monetary management policies put in place for stabilizing the exchange rate of a unit U.S dollar to naira over the years would have been ineffective. Consequently, Zehra et al (2019) stated that the adoption of flexible exchange rate regime among others, have made central banks around the globe to be more concerned about money demand. This was probably intended to ameliorate agricultural financing challenges.…”
Section: Optimal Lag Selectionmentioning
confidence: 99%